An Experimental Evaluation of Transient Flows in a Supersonic Gun Tunnel - Amir, Al-Falahi; Yusoff, M. Z.; Diyar, I. Ahmed (Universiti Malaysia Pahang, 2012)
An experimental study has been performed to investigate transient flows in a supersonic gun tunnel. The experimental work was performed using a short duration high speed flow test facility at the Universiti Tenaga Nasional (UNITEN). A physical description of the facility along with the principles of operation is provided. The pressure history of the flow process was captured using a fast response pressure transducer at three stations located at the end of the facility. Experimental measurements of shock strength, peak pressure and shock wave speed change of Air-Air as a driver/driven gas are then presented and compared with a further set of experimental measurements using the gas combination of Helium-Air. The shock wave speed was measured experimentally with a two pressure transducers technique. The results showed that the existence of the piston has a very significant influence on both the moving shock wave and peak pressure value achieved. The results provide a very good estimate for the above-mentioned parameters obtained after diaphragm rupture, and also provide a better understanding of the parameters that affect the performance of the facility.